Numerical simulation of spectral equipment - Fatkhullin, Timur; Yushkin, Maksim; Panchuk, Vladimir (Acta Astrophysica Taurica, 2025)
We present the results of numerical simulation of high- and low-resolution spectral equipment, as well as its reallife application. A ray-tracing method is implemented in the C++ programming language by using the nVidia CUDA (Compute Unified Device Architecture) technology. The results of simulation for the ground- (BTA/NES, Big Telescope Alt-azimuth Nasmyth Echelle Spectrograph) and space-based (Spectr-UF) spectrographs are exposed. It is shown that the model two-dimensional echelle and long-slit spectra can be used to estimate the energy efficiency of the proposed optical design, to calculate the characteristics of gradient anti-reflection coatings, as well as to create and refine an automatic processing pipeline for observational data long before the launch of space observatories. By using the NES spectrograph simulation, an analysis of the differences between the “ideal” optical design and its real technical implementation is demonstrated. For example, some manufacturing details of the ruled echelle gratings may cause significant differences as compared to expected characteristics. As a result, we show that the implemented mathematical model is a useful and truly powerful tool for designing astronomical spectral equipment, calculating and justifying its basic characteristics, as well as for planning an astrophysical experiment itself.